2016
DOI: 10.1097/ijg.0000000000000193
|View full text |Cite
|
Sign up to set email alerts
|

Through the Looking Glass

Abstract: There is little literature available that investigates glaucoma and its relationship with driving. The few studies that have been conducted are varied in methodology and the results available are highly inconsistent. With an ageing population and heavy reliance on driving for personal mobility, further research into measuring the impact of glaucoma and driving is crucial to ensure a sustained quality of life for the elderly. The potential for future research is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…Older drivers with glaucoma are less confident on roads and modify their driving habits. 17 One cohort study in the United States demonstrated that older drivers with diagnosed glaucoma drove at least safely as their peers without glaucoma and showed no greater crash risks. 23 A Japanese study found that older glaucoma patients show greater driving self-restriction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Older drivers with glaucoma are less confident on roads and modify their driving habits. 17 One cohort study in the United States demonstrated that older drivers with diagnosed glaucoma drove at least safely as their peers without glaucoma and showed no greater crash risks. 23 A Japanese study found that older glaucoma patients show greater driving self-restriction.…”
Section: Discussionmentioning
confidence: 99%
“…The designs of these studies, however, vary significantly, thus impeding the generation of consensus recommendations. 13,[16][17][18] Both findings from the real-world and simulation studies yield conflicts. For example, one French cohort study indicated that glaucoma did not increase crash risk, 19 whereas other studies reported drivers with glaucoma are more prone to traffic crash involvement than those without glaucoma in both the real-world and simulation studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of studies have found that factors, such as older age, female gender, and lower socioeconomic status (SES), are associated with restrictions in driving behavior and ultimately driving cessation (Anstey, Windsor, Luszcz, & Andrews, 2006; Chipman, Payne, & McDonough, 1998; Edwards et al, 2008; Horowitz, Boerner, & Reinhardt, 2002; Meng & Siren, 2015). In addition, age-related vision loss, including decreased visual acuity, contrast sensitivity, and reduced field of vision caused by age-related impairments, such as cataract, glaucoma, and macular degeneration, has been found to be associated with greater difficulties with driving, more driving restrictions, increased accident rates, and greater likelihood of cessation (Agramunt et al, 2016; Blane, 2016; Campbell et al, 1993; Dellinger et al, 2001; Diniz-Filho et al, 2016; McGwin, Chapman, & Owsley, 2000; Owsley et al, 1998; Sengupta et al, 2014). Vision loss is also one of the primary justifications given by older drivers for why they might eventually change their driving behavior and a common reason provided by former drivers for why they stopped driving (Campbell et al, 1993; Dellinger et al, 2001).…”
Section: Vision Loss and Driving Cessationmentioning
confidence: 99%
“…Vários estudos mostraram que pacientes com glaucoma tendem a modificar os seus hábitos de dirigir, como resultado da percepção de dificuldades com a sua visão (52,87) .…”
Section: O Processamento Visual E O Risco Na Condução De Veículos No Glaucomaunclassified